2014
DOI: 10.1017/s0958344014000056
|View full text |Cite
|
Sign up to set email alerts
|

The use of general and specialized corpora as reference sources for academic English writing: A case study

Abstract: Corpora have been suggested as valuable sources for teaching English for academic purposes (EAP). Since previous studies have mainly focused on corpus use in classroom settings, more research is needed to reveal how students react to using corpora on their own and what should be provided to help them become autonomous corpus users, considering that their ultimate goal is to be independent scholars and writers. In the present study, conducted in an engineering lab at a Korean university over 22 weeks, data on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 45 publications
(106 reference statements)
1
61
0
Order By: Relevance
“…In 12 of the studies, the exposure to DDL was more than 5 weeks. It seems that studies by Chang [26] and Muller & Jacobsen [33] lasted for the longest time, which was 22 weeks and 6 months respectively. The studies based on longer-time experiment usually started with a course or project and then presented the research questions to evaluate some aspects of DDL, while the shorter-time study often began with the research question and then create an experimental situation mainly in the form of one-time tests or questionnaires.…”
Section: Research Samples and Designsmentioning
confidence: 96%
See 2 more Smart Citations
“…In 12 of the studies, the exposure to DDL was more than 5 weeks. It seems that studies by Chang [26] and Muller & Jacobsen [33] lasted for the longest time, which was 22 weeks and 6 months respectively. The studies based on longer-time experiment usually started with a course or project and then presented the research questions to evaluate some aspects of DDL, while the shorter-time study often began with the research question and then create an experimental situation mainly in the form of one-time tests or questionnaires.…”
Section: Research Samples and Designsmentioning
confidence: 96%
“…Poole [25] presented the benefits of using a localized, specialized corpus to support various corpus-aided activities in an L2 writing classroom. Chang [26] instructed students to use both a general corpus and a specialized corpus which included journal articles and conference papers in the participants' fields. The findings revealed that a specialized corpus is more helpful as reference sources for EAP students' academic English writing due to its direct relevance to their academic fields.…”
Section: Corpora and Corpus Tools Used In These Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Boulton (2009) claimed the usefulness of the DDL approach in learning and mastering linking adverbs. Emphasizing the importance of choosing the appropriate type of corpus for a particular task, Chang (2014) investigated the roles of both general and specific corpora in improving L2 writing. He conducted a case study to evaluate L2 Korean engineering learners' consultation of both kinds of corpus; results showed a significant effect of using specific corpora as consultation tools in learners' academic writing.…”
Section: Data-driven Learning Approach and Writing Tasksmentioning
confidence: 99%
“…As a result, difficulties have been reported by language learners, who are ill-versed in both target language and metalinguistic knowledge, unfamiliar with complex interfaces and search functions, and feel overwhelmed by voluminous search results. Learners have to master query syntax (e.g., part of speech tags) and the idea of wild cards Chang, 2014;Chen, 2011), spend time analysing copious concordance lines (Boulton, 2010Chambers & O'Sullivan, 2004;Chang, 2014;Daskalovska, 2015;Geluso & Yamaguchi, 2014;O'Sullivan & Chambers, 2006;Yeh, Li, & Liou, 2007;Yoon & Hirvela, 2004), locate collocates in concordances (Chan & Liou, 2005), and interpret the meanings of concordances, mostly in the form of keyword-incontext (KWIC) fragments and incomplete sentences (Geluso & Yamaguchi, 2014;Yoon & Hirvela, 2004). The differing interfaces and functions of corpus analysis further increase the challenge, and learners generally need to learn a new system in order to access a different corpus (Chang, 2014).…”
Section: Concordancers In Collocation Learningmentioning
confidence: 99%